Experimental and numerical investigation of flows inside draft tube of a pump-turbine. Issue 7 (March 2019) - Lai, X D; Liang, Q W; Ye, D X; Chen, X M; Gou, Q Q; Zhang, Q H
Abstract: To determine the flow patterns and validate the flow simulation inside a pump-turbine, Laser Doppler Velocimetry (LDV) measurements and 3D flow simulation in the draft tube of a high-head pump-turbine have been performed at normal operating conditions in turbine and pump modes. Velocity distributions were measured for operating conditions corresponding to the rated head H=600m and the optimum head H=750m at turbine mode for various loads ranging from 40% to 120% of the rated power. The 3D flows through the full pump-turbine model have also been investigated with numerical simulations at all the measured operating points. Both measured and simulated velocity profiles are presented and analyzed to show the influence of operating parameters on the velocity and vortex characteristics in draft tube. Comparison of the measurement and simulation results shows rather good agreement in the vortex-free zone but clear discrepancies at part loads far from BEP. The experimental data such as the velocity profiles, vortex ropes visualization and frequency characteristics of the instantaneous tangential velocity at typical operating points are used to validate the precision of the model and method in the numerical simulation. The presented methodology and techniques in this paper have been demonstrated very helpful in R&D of pump-turbines at two Pumped storage Power plants in China